Kinetics and mechanism of DNA uptake into the cell nucleus - Salman, H. (The National Academy of Sciences, 2001)
Gene transfer to eukaryotic cells requires the uptake of exogenous DNA into the cell nucleus. Except during mitosis, molecular access to the nuclear interior is limited to passage through the nuclear pores. Here we demonstrate the nuclear uptake of extended linear DNA molecules by a combination of fluorescence microscopy and single-molecule manipulation techniques, using the latter to follow uptake kinetics of individual molecules in real time. The assays were carried out on nuclei reconstituted in vitro from extracts of Xenopus eggs, which provide both a complete complement of biochemical factors involved in nuclear protein import, and unobstructed access to the nuclear pores. We find that uptake of DNA is independent of ATP or GTP hydrolysis, but is blocked by wheat germ agglutinin. The kinetics are much slower than would be expected from hydrodynamic considerations. A fit of the data to a simple model suggests femto-Newton forces and a large friction relevant to the uptake process.